2013
DOI: 10.1097/sih.0b013e3182662c69
|View full text |Cite
|
Sign up to set email alerts
|

Practice on an Augmented Reality/Haptic Simulator and Library of Virtual Brains Improves Residents’ Ability to Perform a Ventriculostomy

Abstract: Simulator practice with a library of virtual brains representing a range of anatomies and difficulty levels may improve performance, potentially decreasing complications due to inexpert technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 8 publications
0
99
0
1
Order By: Relevance
“…1,33,62 In the original design, the user holds a haptic stylus beneath a high-resolution stereoscopic display. The haptic feedback combined with the linked motion between the user's hand and corresponding on-screen objects creates a highly realistic surgical simulation.…”
Section: 41mentioning
confidence: 99%
“…1,33,62 In the original design, the user holds a haptic stylus beneath a high-resolution stereoscopic display. The haptic feedback combined with the linked motion between the user's hand and corresponding on-screen objects creates a highly realistic surgical simulation.…”
Section: 41mentioning
confidence: 99%
“…Other tracing systems such as hybrid optical tracker and Wi-Fi signal each could be found one included paper. A paper said using a head-and-hand tracking system but we cannot find the detail technology (Yudkowsky et al, 2012a). One did not use tracking devices because they projected the virtual picture to the manikin.…”
Section: Investigated User Acceptance (2)mentioning
confidence: 99%
“…**The number is the included papers which use this computer system. 3 Papers did not describe computer system (Karthikeyan, Mani, Balasubramaniyan, & Selvam, 2012b;Sakellariou et al, 2009;Yudkowsky et al, 2012a) Three papers did not mention which computing system they used to process the virtual information. Most of included papers (50%) employed laptop as a mobile computing system.…”
Section: Investigated User Acceptance (2)mentioning
confidence: 99%
“…AR has been shown to be an effective tool for gaining laparoscopic suturing skills [24]. Yudkowsky et al [8] reported an AR simulator, which incorporates tomographic images of real patients, to train residents in performing ventriculostomy. HoST takes this technology further by incorporating real surgical experience into teaching more of a true hands-on experience in a safe environment.…”
Section: Skill Typementioning
confidence: 99%
“…Although VR training devices have been shown to be valid and effective for training, their ability remains limited in terms of their representation of a realistic procedure-specific environment [7]. Augmented reality (AR) is an effective alternative that enhances the face validity of training modules [8][9][10]. AR offers a real view of an operating environment in which the events on the field are enhanced and supplemented [11].…”
Section: Introductionmentioning
confidence: 99%